2016
DOI: 10.1080/15504263.2016.1220207
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Disorders: A Challenge for Mexican Community-Based Residential Care Facilities for Substance Use

Abstract: Co-occurring disorders are highly prevalent in community-based residential centers in Mexico and are associated with significantly increased probability of other health risks. This highlights the need to develop care standards for this population and the importance of clinical research in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Individual disorders can progress to more complex disorders or to the development of comorbid disorders which are more difficult to treat, and untreated disorders tend to become more frequent and treatment refractory (Post & Weiss, 1998; Goi et al 2015; Kvitland et al 2016). Dual pathology, defined as the comorbidity of a mental health problem with a substance abuse disorder, is common in Latin American countries (Borruel et al 2010; Marín-Navarrete et al 2016) and creates a public health challenge. Dual pathology is difficult to treat and more likely to recur than less complex conditions (Serfaty, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Individual disorders can progress to more complex disorders or to the development of comorbid disorders which are more difficult to treat, and untreated disorders tend to become more frequent and treatment refractory (Post & Weiss, 1998; Goi et al 2015; Kvitland et al 2016). Dual pathology, defined as the comorbidity of a mental health problem with a substance abuse disorder, is common in Latin American countries (Borruel et al 2010; Marín-Navarrete et al 2016) and creates a public health challenge. Dual pathology is difficult to treat and more likely to recur than less complex conditions (Serfaty, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, we evaluated individuals with polysubstance use in community-based residential care facilities, characterized by high prevalence of CODs ( 19 , 20 ) with the ultimate goal of evaluating the heterogeneity of the associations between internalizing and externalizing CODs on severity of substance use across impulsivity subtypes. To accomplish this, we also carried out the following preliminary steps: (1) to determine the existence of latent impulsivity subtypes of individuals diagnosed with SUD, using LCA; (2) to describe clinical profiles for the different latent classes in two categories: presence of internalizing and externalizing CODs, and severity of substance use (e.g., age of onset, related problems).…”
Section: Introductionmentioning
confidence: 99%
“…However, scientific evidence has shown that the cases of individuals with DDs are the rule rather than the exception (Marín-Navarrete Szerman et al, 2013). Studies performed on the general population estimate a lifetime prevalence of DDs in between 20% and 50% of the cases (Kessler et al, 1996), while studies on the clinical population report lifetime prevalences ranging from 50% to 75% (Marín-Navarrete et al, 2013), and of 40% to 65% in the past 30 days (Substance Abuse and Mental Health Services Administration & Center for Substance Abuse Treatment, 2005;Arias et al, 2013;Marín-Navarrete et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%